Audit pricing and product differentiation in small private firms: evidence from Thailand. Issue 2 (1st July 2014) - Zaman, Mahbub; Chayasombat, Jaravee
Abstract : Purpose: – There is limited evidence on how differences in economic environments affect the demand for and supply of auditing. Research on audit pricing has mainly focused on large client markets in developed economies; in contrast, the purpose of this paper is to focus on the small client segment in the emerging economy of Thailand which offers a choice between auditors of two different qualities. Design/methodology/approach: – This paper is based on a random stratified sample of small clients in Thailand qualifying for audit exemption. The final sample consists of 1, 950 firm-year observations for 2002-2006. Findings: – The authors find evidence of product differentiation in the small client market, suggesting that small firms view certified public accountants as superior and pay a premium for their services. The authors also find that audit fees have a positive significant association with leverage, metropolitan location and client size. Audit risk and audit opinion are not, however, significantly associated with audit fees. Furthermore, the authors find no evidence that clients whose financial year ends in the auditors' busy period pay significantly higher audit fees, and auditors engage in low-balling on initial engagements to attract audit clients. Research limitations/implications: – The research shows the importance of exploring actual decisions regarding audit practice and audit pricing in different institutional and organizational settings. Originality/value: – The paper extends the literature from developed economies and large/listed market setting to the emerging economy and small client market setting. As far as the authors are aware, this is the first paper to examine audit pricing in the small client market in an emerging economy.